The Sociology of Prayer: Dimensions and Mechanisms - Paul Froese (Social Sciences, 2021)
The sociology of prayer has a long history and routinely stresses the centrality of prayer to religious belief and ritual solidarity. Still, we have struggled to clearly define the parameters of prayer and the various components of this ubiquitous practice. Drawing from a comprehensive literature review of prayer research, we propose that there are four conceptually distinct dimensions of the private prayer experience which vary across religious cultures and traditions; they are (1) the quantity of prayer, (2) the style of prayer, (3) the purpose of prayer, and (4) prayer targets. Our proposed measures of these dimensions offer researchers a framework to better theorize and investigate the social mechanisms which produce variation in prayer as well as the individual and social outcomes of prayer. In particular, we discuss how each prayer dimension fits within specific theoretical framings to better test the extent to which the emotional, rational, and behavioral elements matter to prayer outcomes.